Effect of Project Based Learning Method on Students ‘Academic Performance in Mathematics Subject in Rwanda - Iradukunda, Alice; Andala, Hesbon (African Journal of Education and Practice, 2024)
Purpose: The purpose of this study was to evaluate the effect of project-based learning (PBL) on students’ academic performance in mathematics at TTC Muhanga, located in Muhanga District, Southern Province. Methodology: A descriptive research design was employed, involving 889 participants, including 273 student teachers, 23 teachers, 1 dean, and 1 principal. The study ensured reliability through test-retest and Cronbach’s alpha methods, while content validity was assessed using the Content Validity Index (CVI). Data were gathered through questionnaires and interviews and analyzed using SPSS. Findings: The findings reveal a generally positive perception of PBL practices. Collaborative projects were particularly well received, with 73.9% of teachers agreeing that they enhance communication (mean score: 4.61). Hands-on activities were also endorsed by 69.56% of participants (mean score: 4.48), while technology integration received less consensus, with 60.87% agreeing on its effectiveness (mean score: 4.30). Reflection and presentation skills were highlighted as especially impactful, with 78.26% of respondents strongly agreeing (mean score: 4.65). The study further demonstrates that both collaboration (r = .904, β = .500) and technology use (r = .677, β = .553) significantly contribute to increased student engagement and improved academic performance. Unique Contribution to Theory, Practice and Policy: Based on these findings, the study recommends enhancing technology integration within PBL, promoting continuous professional development for teachers, emphasizing the importance of collaboration in PBL activities, and increasing opportunities for students to engage in reflection and develop presentation skills.